PENGARUH DISIPLIN KERJA, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP MOTIVASI KERJA KARYAWAN PT. ATHA MARTH NAHA KRAMO MALINAU KALIMANTAN UTARA - oktorius oktorius (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This study aims to determine (1) The Effect of Work Discipline Against Employee Motivation, (2) Work Environment Against Employee Motivation and (3) Compensation Against Employee Motivation. Effect of Work Discipline, Work Environment, and Compensation Together Against Employee Motivation PT. Atha Marth Naha Kramo Malinau North Borneo. This study used a type of kauntitaf research. Population in this research that is PT. Atha Marth Naha Kramo Malinau North Kalimantan, amounting to 300 people. The variables of this research are work dispersion (X1), work environment (X2), compensation (X3) and work motivation (Y). This research technique using porposive sampling.Methods of data collection using questionnaires. The results showed that the multiple linear regression equation is Y = 0.024 X1 - 0.115 X2 + 1.084 X3 + error. Simultaneously Discipline Work (X1), Work Environment (X2), and Compensation (X3) influence on Employee Motivation PT. AMNK. Partially variable Discipline Work, Work Environment and Compensation have a significant effect on Employee Motivation PT. AMNK